(untitled) (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2025)
The city of Pekanbaru has a prevalence of mental disorders, stress, and depression of 5.67% of its population. Efforts that can be made to improve people’s mental health from the aspect of spatial planning are to optimize the function of the Green Open Space (RTH). RTH Kaca Mayang is a public space that the people of Pekanbaru City commonly use. This study aims to analyze the role of RTH Kaca Mayang in improving the mental health of the people of Pekanbaru City. This study examines the accuracy and suitability indicators of the current condition of the Kaca Mayang RTH, with a focus on environmental quality, accessibility, facility satisfaction, mental health benefits, and social engagement. Data analysis was qualitatively descriptive and reviewed previous research with a mixed approach, involving non-participative and participatory methods. The results of this study show that aspects of environmental quality, accessibility, and facility satisfaction received good assessments from respondents. Meanwhile, from the aspect of mental health benefits in society and social involvement with fellow communities, the RTH benefit variable in stress reduction received a fairly good assessment. All the results of the assessment and score were obtained from the community’s own perception and response when carrying out activities on RTH Kaca Mayang. The final results of this study show that the green open space of Kaca Mayang is effective in reducing stress, improving mood, and providing a sense of security, although the relevant government needs to improve in terms of security, facilities, and social participation. In short, it can be said that good management of green areas can be an effective solution to mental health problems in cities.